Bilobalide attenuates hypoxia induced oxidative stress, inflammation, and mitochondrial dysfunctions in 3T3-L1 adipocytes via its antioxidant potential. (2014) - Priyanka, A.; Nisha, V. M.; Anusree, S. S.; Raghu, K. G.
Abstract Excessive expansion of white adipose tissue leads to hypoxia which is considered as a key factor responsible for adipose tissue dysfunction in obesity. Hypoxia induces inflammation, insulin resistance, and other obesity related complications. So the hypoxia-signalling pathway is expected to provide a new target for the treatment of obesity-associated complications. Inhibition or downregulation of the HIF-1 pathway could be an effective target for the treatment of obesity related hypoxia. In the present study, we evaluated the effect of hypoxia on functions of 3T3-L1 adipocytes emphasising on oxidative stress, antioxidant status, inflammation and mitochondrial functions. We have also evaluated the protective role of bilobalide, a bioactive from Gingko biloba, on hypoxia induced alterations. The results revealed that hypoxia significantly altered all the vital parameters of adipocyte biology like HIF-1α expression (103.47% ↑), lactate and glycerol release (184.34% and 69.1% ↑, respectively), reactive oxygen species (ROS) production (432.53% ↑), lipid and protein oxidation (376.6% and 566.6% ↑, respectively), reduction in antioxidant enzymes (superoxide dismutase and catalase) status, secretion of inflammatory markers (TNF-α, IL-6, IL-1β and IFN-γ) and mitochondrial functions (mitochondrial mass, membrane potential, permeability transition pore integrity, superoxide generation). Bilobalide significantly protected adipocytes from adverse effects of hypoxia in a dose-dependent manner by attenuating oxidative stress, inflammation and protecting mitochondria. Acriflavine (HIF-1 inhibitor) was used as positive control. On the basis of this study, a detailed investigation is needed to delineate the mechanism of action of bilobalide to develop it as therapeutic target for obesity.